2023
DOI: 10.1371/journal.pone.0289888
|View full text |Cite
|
Sign up to set email alerts
|

Role demands and turnover intention among Covid-19 frontline nurses: The mediating and moderating roles of compassion fatigue and spiritual leadership

Abstract: The working conditions created by the Covid-19 pandemic have been proven to amplify frontline nurses’ desire to leave their profession in recent years; thus, exploring new causing variables is vital. This cross-sectional study examined role demands’ direct and indirect effects on turnover intention through compassion fatigue and tested the various dimensions of spiritual leadership as moderators on the relationship between compassion fatigue and turnover intention. A total of 527 valid responses were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Nurses who do not work directly with COVID patients have higher occupational satisfaction than those who do. Nurses who care for COVID patients experience more emotional burnout and consider leaving the profession more frequently than other nurses [41,64,68,69]. In addition, working conditions during the pandemic negatively affect the professional commitment of healthcare professionals [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses who do not work directly with COVID patients have higher occupational satisfaction than those who do. Nurses who care for COVID patients experience more emotional burnout and consider leaving the profession more frequently than other nurses [41,64,68,69]. In addition, working conditions during the pandemic negatively affect the professional commitment of healthcare professionals [20].…”
Section: Discussionmentioning
confidence: 99%
“…However, these researchers have focused on the psychological effects of the pandemic on nurses' work environment but have not determined its effect on professional commitment. Given the global nurse shortage, we think that we should take steps to improve nurses' professional commitment to keep them in the profession [18,[39][40][41]. Therefore, this study aimed to determine whether burnout affected nurses' professional commitment during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Long working hours, shift work, and increased workload were related to the physical and psychological pain of nurses ( Liu et al, 2020 ). Studies have shown that when nurses have role conflicts, their happiness decreases, work pressure increases, negative emotions for work increase, and turnover intention increases ( Kachie et al, 2023 ). Good role cognition helps to improve the negative emotions, role stress, and subjective experience of nurses ( Chen and Changying, 2019 ).…”
Section: Methodsmentioning
confidence: 99%